2000
DOI: 10.1592/phco.20.1.13.34667
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐Associated Lipodystrophy Syndrome

Abstract: Highly active antiretroviral therapy (HAART) for human immunodeficiency virus-1 (HIV-1) and prophylactic therapy for opportunistic infections have increased survival. Adverse effects of HAART include lipid profile alterations, diabetes mellitus, and fat redistribution. These metabolic and physical changes are called the HIV-associated lipodystrophy syndrome. A link to protease inhibitors has been suggested, and more recently to nucleoside reverse transcriptase inhibitors and factors related to duration of HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…The cause of this syndrome is not clear but seems to be multifactorial. The HIV-1 infection itself seems to contribute to the development of these pathologic changes or increases the vulnerability of patients to develop the syndrome upon uptake of anti-HIV-1 drugs; some AIDS patients develop the characteristic features and metabolic disturbances of the syndrome before treatment (26,51,52). Our results suggest that Vpr might contribute to the insulin resistance of AIDS patients through both its FOXO-related insulin action blockade and its previously described glucocorticoid receptor coactivator activity (12,13).…”
Section: Discussionmentioning
confidence: 63%
“…The cause of this syndrome is not clear but seems to be multifactorial. The HIV-1 infection itself seems to contribute to the development of these pathologic changes or increases the vulnerability of patients to develop the syndrome upon uptake of anti-HIV-1 drugs; some AIDS patients develop the characteristic features and metabolic disturbances of the syndrome before treatment (26,51,52). Our results suggest that Vpr might contribute to the insulin resistance of AIDS patients through both its FOXO-related insulin action blockade and its previously described glucocorticoid receptor coactivator activity (12,13).…”
Section: Discussionmentioning
confidence: 63%
“…It has recently been reported that long-term HAART is associated with metabolic side-effects, such as lipodystrophy (Carr et al, 1998;Qaqish et al, 2000). Development of lipodystrophy is linked to the use of protease inhibitors, though it was also reported in patients receiving only RT inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…1 HAART has been associated with numerous affects on lipid metabolism, including subcutaneous fat wasting, abdominal obesity, insulin resistance, and hyperlipidemia. 2,3 Metabolic complications arising from HAART may be due to drug-drug interactions, exacerbation of preexisting conditions, reconstitution of immune system function, or a combination. 2,3 Studies of hyperlipidemia in HIV-infected persons are complicated because dyslipidemia may occur in the absence of therapy (reviewed in Safrin and Grunfeld 3 ).…”
mentioning
confidence: 99%
“…2,3 Studies of hyperlipidemia in HIV-infected persons are complicated because dyslipidemia may occur in the absence of therapy (reviewed in Safrin and Grunfeld 3 ). Although HIV infection itself and treatment with reverse transcriptase inhibitors have been associated with altered metabolism, [2][3][4][5][6] substantial evidence indicates a role for some PIs in causing metabolic complications.…”
mentioning
confidence: 99%